Knowledge Level of COVID-19 Prevention in Banjar Gambang Communities, Seraya Village, Karangasem, Indonesia (Althea Medical Journal, 2023)
Background: Problems to COVID-19 are closely related to the level of knowledge and community prevention. Therefore, to overcome COVID-19, increased knowledge and prevention are needed. This study aimed to evaluate the correlation between prevention and knowledge level about COVID-19.Methods: A cross-sectional study using a convenience sampling approach was conducted in Banjar Gambang, Karangasem, Indonesia, in April 2022. The knowledge level and preventive behavior towards COVID-19 were measured using the COVID-19 Preventive Behaviors Index (CPBI) and the knowledge, attitudes, and practice toward COVID-19 (KAPCOV-19) questionnaire. The data were analyzed using SPSS software version 26.0.Results: A total of 52 respondents were included, who had excellent level of knowledge (44.2%) and moderate prevention behaviour (48.1%). A strong and significant correlation was found between the preventive index and the knowledge levels of COVID-19 (r = 0.548; p
Keywords: COVID-19; preventive behaviors index; knowledge; KAPCOV-19